Simultaneous Determination of Hydrochlorothiazide and Enalapril Maleate in Pharmaceutical Formulations Using Fourier Transform Infrared Spectrometry - Seyyed Hamid Ahmadi; Hassan Tavakoli; Majid Amirzadeh; Mohammad Reza Sangi (Iranian Journal of Chemistry & Chemical Engineering, 2014)
A new Fourier Transform-Infra Red (FT-IR) spectrometric method was developed for assaying hydrochlorothiazide (HCT) and enalapril maleate (ENM) in binary solid pharmaceutical formulations. Multivariate Partial Least Squares (PLS) method was used for calibration of derivative spectral data. Acetonitrile was used as solvent due to its spectral transparency and adequate solubility of analytes in it. A 4- levels full factorial design of binary standard solutions of HCT and ENM were prepared and used for calibration in the spectral range of 1550-1800 cm-1. Statistical parameters such as correlation coefficient(R), Standard Error of Estimation (SEE), Standard Error of Prediction (SEP), and Standard Error of Cross Validation (SECV) have been evaluated and used for selecting of optimizing of parameters. Correlation coefficients were 0.9990 and 0.9995 and Relative Standard Deviation (RSD) were 1.97% and 1.35% (n=5) for HCT and ENM, respectively. Detection limits of ENM and HCT were obtained 0.54 and 0.99 mg/mL respectively. The proposed methods were successfully applied to the determination of the over mentioned drugs in laboratory-prepared mixtures and in commercial tablets. This method has suitable accuracy, precision, repeatability and is comparable with reference standard methods.